Association between dietary intake of flavonoids and hyperuricemia: a cross-sectional study - Houlin Li; Lin Shi; Xuelan Chen; Mo Wang (BMC, 2023)
Abstract Background Previous research has demonstrated flavonoid intake was closely related to hyperuricemia. The purpose of this study was to examine whether flavonoid intake was associated with serum uric acid and hyperuricemia in U.S. adults. Methods The study sample consisted of 8,760 participants enrolled in the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2010. Flavonoid consumption was measured using a two-day recall questionnaire on dietary intake. Hyperuricemia was defined based on the serum uric acid levels, determined as ≥ 7 mg/dL for males and ≥ 6 mg/dL for females. The study utilized multivariate linear regression to determine the correlation between flavonoid consumption and serum uric acid levels. Additionally, analyses involving multivariate logistic regression and restricted cubic splines (RCS) were conducted to evaluate the potential link between flavonoid consumption and hyperuricemia. All analyses were adjusted for possible confounding variables. Results The study revealed a negative correlation between serum uric acid levels and elevated levels of anthocyanidins and flavanones, with significant p-trends of < 0.001 and 0.02 respectively. The multivariate analysis showed that anthocyanidins and flavanones intake had a significant negative association with the risk of hyperuricemia, with p-trend value being < 0.001 and 0.01, respectively. Flavan-3-ols, flavonols, and all flavonoids exhibited a non-linear association with the incidence of hyperuricemia, with significant p-nonlinear values of < 0.001, 0.04, and 0.01 respectively. Conclusion Our study demonstrated that individuals who follow a diet rich in anthocyanins and flavanones had significantly lower serum uric acid levels and a lower incidence of hyperuricemia.